Where is the best site for embryo transfer? A study of relation of embryo-fundal distance with pregnancy rate in ICSI-ET cycle - Tanksale, Shreedevi J.; Nadkarni, Purnima K.; Nadkarni, Aditi A.; Singh, Prabhakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Embryo transfer is the ultimate and most critical step of IVF-ICSI treatment cycle. It has a significant impact on the success rate of IVF cycle. Undoubtedly, it has significant impact of the pregnancy rate and implantation rate. Along with the other factors the impact of the site of embryo transfer has also been studied by several investigators. There is lack of clear consensus about the ideal site of embryo transfer. Methods: This study includes a retrospective analysis of 200 embryo transfers done in 200 infertile couples done at our infertility clinics from January 2016 to March 2016. Transfer cycles of gamete donation, embryo donation and frozen embryos were excluded from the study. The study involved patients undergoing their first IVF- ICSI cycle with fresh embryo transfer at our IVF Unit. All patients were stimulated using Antagonist protocol starting Gonadotropins from day 2/3 of menses. Results: The clinical pregnancy rate was highest (55.2%) in group 2 when the embryo fundal distance was more than 10 mm but less than or equal to 15 mm. In group 3 when embryos were placed beyond 15 mm distance from the fundus, the clinical pregnancy rate was 34.66%. The lowest pregnancy rate - 30% was found in group 1 when embryos were places less than 10 mm from fundus. There was only a single case of ectopic pregnancy in the study group. The ectopic pregnancy was seen in group 1. There two cases of abortion each in group 2. The miscarriage rate was higher in group 3-5. 33% as compared to 1.9% in group 2. The sample size was small to determine if these results were significant enough. Conclusions: The present study demonstrates that higher pregnancy rates are obtained if the embryos are selectively placed at a distance between 10mm to 15 mm from the fundal endometrial surface. It is not possible to determine exact location of embryo placed in utero by any method. The findings of our study can be considered as a guiding force by clinicians.